What factors affect teacher professional learning: a qualitative meta-analysis based on the Onion model - Hanqiang Li (Quality Education for All)
Purpose – Current academic research on teacher learning is increasing in number and deepening in quality, but at the same time, the heterogeneity is growing significantly. Similar work is challenging to cross-check regarding conclusions due to the different research foci. This paper aims to provide a reliable theoretical framework and offers solid insights based on the existing research. Design/methodology/approach – Based on the Onion model, 67 core literature in English and Chinese were coded through qualitative meta-analysis methods to explore environmental, behavioral, competence, belief, identity, mission and other factors that may impact teacher learning. Findings – It was found that the quantitative structure of the current relevant studies was in an inverted triangular shape with three levels of steps, respectively, which can be summarized as structural environment, core behaviors and dominant mission. The heterogeneity between the findings mainly originated from two situations, oppositional and complementary and some structural adjustments were made to the Onion model according to the coding results to better represent the interaction of influences between the levels. It also analyzes current research trends and the centrality of learned behaviors based on the coding results. Social implications – The design of teacher learning activities should combine theoretical, practical and inquiry learning to ensure that teachers are kept fresh and motivated by sustained and varied stimuli. Originality/value – To the best of the authors’ knowledge, this study is the first to analyze teacher learning influences through qualitative meta-analysis and create node saturation to analyze the results, resulting in highly credible and valuable research findings.